Manajemen Kurikulum Perguruan Tinggi Pesantren Melaui Lean Concept Dalam Memenuhi Harapan Pelanggan - Rohman, Ahmad Rifdur (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
Curriculum management in pesantren based higher education requires an approach that is not only managerially effective but also aligned with the fundamental aims of Islamic education, particularly the formation of faithful, knowledgeable, and well-mannered individuals (ta’dīb). This study critically examines the application of the lean concept in curriculum management within pesantren based higher education by positioning Islamic educational values as the primary analytical framework. Lean principles such as value stream mapping, waste reduction, and continuous improvement are not adopted mechanistically; instead, they are critically reinterpreted and adapted to correspond with Islamic values, pesantren traditions, and moral educational objectives. In this context, “value” is not defined merely in terms of customer satisfaction, but as educational benefit (maṣlaḥah) encompassing spiritual development, intellectual integrity, and the social relevance of graduates. This study employs a qualitative approach through literature review and conceptual analysis to explore the intersection between lean-based modern management and the philosophical foundations of pesantren education. The findings indicate that the lean concept can enhance the effectiveness and quality of pesantren curricula when it is reoriented from market-driven efficiency toward strengthening ta’dīb, ensuring sustainable learning processes, and reinforcing the moral responsibility of Islamic educational institutions. This study affirms that integrating modern management frameworks with pesantren values enables curriculum development that is both efficient and distinctly Islamic, thereby contributing to contemporary scholarship in Islamic educational management.